2011
DOI: 10.1002/mabi.201000434
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antitumoral Activity of Gelatin/Polyoxometalate Hybrid Nanoparticles

Abstract: Surfactant-free gelatin/heptamolybdate (HM) hybrid nanoparticles are prepared by a simple and environmentally friendly approach utilizing the electrostatic interaction between anionic HM and the zwitterionic gelatin. The obtained nanoparticles have a tunable size and very high HM loading content up to about 70%. In vitro and in vivo experiments prove that the gelatin/HM hybrid nanoparticles exhibit significantly better antitumor activity than plain ammonium heptamolybdate solution. Therefore, the gelatin/HM hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Despite their negative charge, several proof‐of‐concept studies showed that POMs can cross cell membranes, with or without the involvement of carrier systems, to be mainly localized in the cytoplasm . Their biological activity mainly stems from the redox behavior, which makes them excellent electron acceptors, and from the capability to interact with biological macromolecules through electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Despite their negative charge, several proof‐of‐concept studies showed that POMs can cross cell membranes, with or without the involvement of carrier systems, to be mainly localized in the cytoplasm . Their biological activity mainly stems from the redox behavior, which makes them excellent electron acceptors, and from the capability to interact with biological macromolecules through electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%
“…CS is a linear polysaccharide constituted of b-(1,4)-D-glucosamine units, obtained from deacetylation of a naturally abundant biopolymer, chitin, which is the main constituent of the exoskeleton of crustaceans and cell wall of various fungi. Due to its availability, ease of preparation, excellent metal coordination [18] and particles stabilization capabilities [19,20], CS has found application in various research field such as biomedical sciences [21][22][23], food preservation [24,25] and water treatment [26][27][28][29][30][31]. CS has been reported to suit water disinfection applications when incorporated into membranes, sponges, or surface coatings of water storage systems [31].…”
Section: Introductionmentioning
confidence: 99%
“…Compounds 2 , 2+ , and 2+POM showed 1 O 2 photogeneration that was almost identical to that of MB (standard 1 O 2 acceptor) [64,65] . Interestingly, 2+POM and 3+POM showed slightly lower 1 O 2 photogeneration than 2 and 2+ and 3 and 3+ in the absence of tumour cells; however, the POM complexes showed better or comparable PDT activity compared with free forms (neutral and cationic PSs), which indicates that the enhanced photodynamic activity of POM complexes based‐on the good delivery effect of POM results from the high cellular penetration and localisation of the purpurinimide moieties of POM complexes in tumour cells via endocytosis, as compared to free purpurinimides [41,66] …”
Section: Resultsmentioning
confidence: 88%
“…POMs, which are metal‐oxygen cluster anions, are functional molecules extensively used in various applications owing to their favourable catalytic, photochemical, and electrical properties [37–39] . Importantly, there are very rare biomaterial applications of POM‐based supramolecular materials those built on electrostatic interactions [40–44] . In a previous report, [36] we demonstrated a chlorin–POM supramolecular complex that showed enhanced photodynamic activity compared to free chlorin.…”
Section: Introductionmentioning
confidence: 90%